AN INVESTIGATION OF EFFECTS OF MATERNAL BMI ON COURSE AND RESULT OF LABOUR IN PRIMIGRAVIDAE PATIENTS: A CROSS-SECTIONAL STUDY. - Samarina Kamal (Student’s Journal of Health Research Africa, 2024)
Background The purpose of this research is to determine how higher BMI affects labor outcomes in primigravida pregnant women. Methods 200 fully developed single primigravida pregnant women who arrived at the labor unit during the active stage of labor participated in a cross-sectional investigation. The patients were separated into three equal categories according to their BMI: those with an average body mass index (group I), those who were overweight (group II), and those who had class I obesity (group III). Results A considerable higher risk of C-section (C.S.) was discovered to be linked with elevated BMI (13% in group I, 18% in group II, and 40% in group III). Higher BMI women who gave birth vaginally experienced much longer 1st and 2nd stages of labor, which raised the demand for oxytocin boost and dosage. Significantly higher chances of postoperative sepsis, perineal rips, wound infection, significantly higher birth weights, and longer stays in the neonatal unit (NNU) are associated with these mother and fetal results. Conclusion Maternal obese primigravida women were more likely to get worse than ideal results. In addition, there has been a rise in the incidence of C.S. and protracted first and second phases of labor. Recommendations To improve labor outcomes in primigravida women with higher BMI, it is recommended to implement targeted weight management programs for women of childbearing age to reduce BMI before pregnancy. Additionally, enhancing prenatal care protocols for obese primigravida women is essential to monitor and mitigate the risks associated with high BMI during labor. These steps can help in reducing the incidence of C-sections, protracted labor stages, and associated maternal and fetal complications.